2013
DOI: 10.1038/jid.2012.272
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Facilitates Melanoma Lymph Node Metastasis by Influencing Tumor Lymphangiogenesis

Abstract: Alterations in epidermal growth factor (EGF) expression are known to be of prognostic relevance in human melanoma, but EGF-mediated effects on melanoma have not been extensively studied. As lymph node metastasis usually represents the first major step in melanoma progression, we were trying to identify a potential role of primary tumor-derived EGF in the mediation of melanoma lymph node metastases. Stable EGF knockdown (EGFkd) in EGF-high (M24met) and EGF-low (A375) expressing melanoma cells was generated. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 42 publications
0
59
0
1
Order By: Relevance
“…In tumor cells, EGF may mediate proliferation by activating the EGF receptor pathway which leads to tumor cells survival and metastasis (18). Previous studies demonstrated that EGF is able to induce tumor metastasis through matrix metalloproteinases (19), tyrosine kinase PK2 (20), Podoplanin (21), Rictor binding protein (22), epithelial mesenchymal transition (23) and improving blood vessel (24) and lymph gland growth (25,26). In the present study, the mRNA level of EGF was significantly upregulated in patients with lymph node metastasis, which indicated that EGF may be associated with lymph node metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, EGF may mediate proliferation by activating the EGF receptor pathway which leads to tumor cells survival and metastasis (18). Previous studies demonstrated that EGF is able to induce tumor metastasis through matrix metalloproteinases (19), tyrosine kinase PK2 (20), Podoplanin (21), Rictor binding protein (22), epithelial mesenchymal transition (23) and improving blood vessel (24) and lymph gland growth (25,26). In the present study, the mRNA level of EGF was significantly upregulated in patients with lymph node metastasis, which indicated that EGF may be associated with lymph node metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bracher et al (46) demonstrated that EGF has a pro-metastatic effect, with EGF serum levels being significantly higher in patients with metastases than in those without metastases. EGF belongs to a family of growth factor capable of activating the specific receptor EGFR.…”
Section: Growth Factors In Malignant Melanomamentioning
confidence: 99%
“…Also, EGF is positively correlated with VEGF-C and PROX-1 expressions in the human primary melanoma, although in vivo EGF knockdown significantly decreases VEGF-C expression. Thus, it can be pointed out that EGF seems to play an important role in malignant melanomaassociated lymphangiogenesis (46,47).…”
Section: Growth Factors In Malignant Melanomamentioning
confidence: 99%
“…The dysregulation of this axis has been particularly linked to cancer development, and also to several other diseases and their pathogenesis. Therefore, in addition to a number of epithelial cancers [8][9][10][16][17][18][19][23][24][25]31], some other diseases might also be benefited with the proposed strategy of stratification.…”
Section: Clinical Implications Of the Findingsmentioning
confidence: 99%
“…As a result of this analysis, a novel stratification method was proposed, which overcomes the variability observed in the conventional method of stratification. It is worth to notice that, despite this study was performed in healthy donors, its findings could be relevant for the stratification of patients by sEGF levels, in diseases for which the usefulness of this molecule as a biomarker has been previously established: in diagnosis [15][16][17], prognosis [18,19], determination of patient's eligibility for treatment [20][21][22] and monitoring of the therapy in a clinical setting [17,[23][24][25][26]. The results of the present study might also help to understand the kinetics of the release of EGF by the platelets, thus contributing to a better reading of the levels of this molecule in sera of healthy and sick individuals.…”
Section: Introductionmentioning
confidence: 99%